Handling Food Vulnerability Strategy Through Non-Cash Food Assistance Program (BPNT) in Denpasar City, Bali Province - I Made Yoga Jaya Kusuma; Erfan Wahyudi; Marzuki (Yayasan Hisnul Muslim Lombok, 2024)
The Non-Cash Food Assistance Program (BPNT) in Denpasar City, Bali Province, has formulated an effective strategy for handling food insecurity by adopting an information technology-based approach and coordinating Social Service employees. This strategy focuses on improving employee performance and competency, information technology infrastructure, distribution centers, and optimizing transportation aspects. Through this approach, distribution points in sub-district or sub-district centers are encouraged to strengthen the inclusive approach promoted by this program. However, obstacles in program implementation are critical points that require serious attention. Problems related to unregistered beneficiaries and changes in KPM addresses are the main challenges in maintaining smooth BPNT distribution. In addition, uncertainty due to inconsistent distribution of funds every month creates a difficult situation for beneficiaries. Technical obstacles, such as the availability of stock at E-Warong and technical problems with the EDC machine, also add to the complexity of implementing the program. To overcome these obstacles, measurable and sustainable solutions are needed. Steps such as conducting direct visits to beneficiary homes to ensure data validity and preventing input errors, labeling KPM homes to reduce overlap, and close collaboration between the Social Service and Dukcapil Service to update data, are solutions that can improve effectiveness and efficiency of the BPNT program in Denpasar City. By implementing these steps, it is hoped that this program can continue to run better and have a greater positive impact in dealing with food insecurity in the region.